Entre saberes docentes e práticas pedagógicas: um processo formativo sobre a alfabetização de crianças com deficiência intelectual - Silva, Andrialex William da (2024)
Discussions on teacher training are wide-ranging in the educational field, with literacy and Special Education being frequent themes. The study developed here aligns the three themes, thinking specifically about the continuing education of literacy teachers in inclusive contexts with students with intellectual disabilities. In this sense, the main objective is to analyze continuing teacher education in the field of literacy for children with intellectual disabilities, considering its possible contributions to teaching knowledge and pedagogical practice. The research approaches disability from the social model, considering the learning potential of students with intellectual disabilities and the need to think about literacy practices from the perspective of literacy that include the student in the context of the regular school; in the field of continuing education, with regard to literacy and special education, the study understands that training proposals need to be aligned with the reality of the educational context, promote spaces for reflection, and encourage critical and reflective thinking. With this in mind, this qualitative, interventional study investigated a continuing education course for public school teachers in the state of Rio Grande do Norte, which focused on the literacy of students with intellectual disabilities. As a result, we identified that the space for ongoing training can move teaching knowledge in such a way as to bring about qualitative gains, such as broadening the understanding of school inclusion, refining what is meant by intellectual disability and reorganizing what is read about literacy. We understand that a change in teaching knowledge can have an impact on pedagogical practice. In this sense, still in the research findings, we mapped didactic proposals that took two curricular paths: the first, individualizing literacy practices, which make use of adaptations in the curriculum aimed at the learning of students with intellectual disabilities; the second; universalizing proposals, draws practices that when considering an open curriculum, avoid differentiations with activities that contemplate the diversity of the students. Finally, we understand continuing education in the field of literacy for students with intellectual disabilities as a necessary space for maintaining teaching knowledge and reflecting on pedagogical practice, arguing that there is an intimate relationship between these two elements.